Implementation of Green Campus to Realizing University Social Responsibility at State Islamic Religious College (SIRC) in South Sulawesi Indonesia - Muhammad Wahyuddin Abdullah,; Bayan, Andi Yustika Manrimawagau; Hanafie, Hadriana (Technium Social Sciences Journal, 2021)
The purpose of research to find out the extent implementation of green campus at SIRC in South-Sulawesi Indonesia which 4 institutes namely Alauddin State Islamic University, Pare-pare State Islamic Institute, Bone State Islamic Institute and Palopo State Islamic Institute. This is qualitative research with phenomenological approach. The results show that SIRC South-Sulawesi Indonesia has fulfilled its responsibility carrying out the university's responsibility to environment. While Implementation of green campus in SIRC South Sulawesi hasn’t been done well. But SIRC strives be green-insightful tourist campus. Look from strategic plan have compiled to achieve all plans prepared especially to create green campus.